Mechanisms underlying reduced P2Y1‐receptor‐mediated relaxation in superior mesenteric arteries from long‐term streptozotocin‐induced diabetic rats. (4th August 2012) - Ishida, K.; Matsumoto, T.; Taguchi, K.; Kamata, K.; Kobayashi, T.
Abstract Aim Extracellular nucleotides activate cell‐surface purinergic (P2) receptors, contribute to the local regulation of vascular tone and play important roles in pathophysiological states. However, little is known about the vasodilator effects of P2Y1‐receptor activation in diabetic states. We hypothesized that in a model of established type 1 diabetes, long‐term streptozotocin (STZ)‐induced diabetic rats, the arterial relaxation elicited by a P2Y1‐receptor agonist would be impaired. Methods Relaxations to adenosine 5′‐diphosphate sodium salt (ADP), 2‐MeSADP (selective P2Y1‐receptor agonist) and adenosine 5′‐triphosphate disodium salt (ATP) were examined in superior mesenteric artery rings from long‐term STZ‐induced diabetic rats (at 50–57 weeks after STZ injection). ADP‐stimulated nitric oxide (NO) production in the superior mesenteric artery was assessed by measuring the levels of NO metabolites. Mesenteric artery expressions of P2Y1 receptor, and ADP‐stimulated levels of phosphorylated endothelial NO synthase (eNOS) (at Ser1177 and at Thr495) and eNOS were detected by Western blotting. Results Arteries from diabetic rats exhibited (vs. those from age‐matched control rats): (i) reduced ADP‐induced relaxation, which was partly or completely inhibited by endothelial denudation, by NOS inhibitor treatment and by a selective P2Y1‐receptor antagonist, (ii) reduced 2‐MeSADP‐induced relaxation, (iii) reduced ADP‐stimulated release of NO metabolites and (iv) impaired ADP‐induced stimulation of eNOS activity (as evidenced by reduced the fold increase in eNOS phosphorylation at Ser1177 with no difference in fold increase in eNOS phosphorylation at Thr495). The protein expression of P2Y1 receptor did not differ between diabetic and control arteries. Conclusions These results suggest that P2Y1‐receptor‐mediated vasodilatation is impaired in superior mesenteric arteries from long‐term type 1 diabetic rats. This impairment is because of reduced P2Y1‐receptor‐mediated NO signalling, rather than to reduced P2Y1‐receptor expression.